Qualität der Lehrerbildung an der Universität – Lehrerbefragung zur Ausbildung in Geographie, Geographiedidaktik und in den Erziehungswissenschaften in Bayern - Hemmer, Ingrid; Obermaier, Gabriele (Zeitschrift für Geographiedidaktik (ZGD), 2003)
Young teachers were questioned about the quality of their training. The central questions were: How much importance do you attach to your university training in the fields of Geography, Geographical Education and Educational Sciences? How satisfied are you with your training in these fields? Which improvements would you suggest? The judgements of the young teachers were compared with those of the seminar teachers, which had been determined in an earlier survey. All three fields are considered to be highly important. The training in all three fields is considered to be unsatisfactory. Geography would have to offer more methodology and regional geography. Geographical Education should offer more new teaching methods, computer training and didactics for field trips. The Educational Sciences should supply more problemoriented case studies. Concerning the geographical education training, a comparison of the young teachers’ judgement with that of the seminar teachers showed that the seminar teachers attach a bit more importance to the training than the young teachers do. The satisfaction, however, does not differ. The importance of the training in Geography received the same judgement from both groups. The seminar teachers, however, are significantly less satisfied than the young teachers.